2008
DOI: 10.1016/j.cub.2008.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Depth Affects Where We Look

Abstract: Understanding how we spontaneously scan the visual world through eye movements is crucial for characterizing both the strategies and inputs of vision. Despite the importance of the third or depth dimension for perception and action, little is known about how the specifically three-dimensional aspects of scenes affect looking behavior. Here we show that three-dimensional surface orientation has a surprisingly large effect on spontaneous exploration, and we demonstrate that a simple rule predicts eye movements g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Our results for saccades extend those recently published by Wexler and Ouarti (2008), who showed that spontaneous saccade directions follow the tilt axis of an inclined plane, for a variety of depth cues that were presented singly (other recent work that reports compatible results is Jansen, Onat, & König, 2009). The fact that spontaneous saccade directions are aligned with the surface depth gradient of a purely disparity-defined plane as shown by Wexler and Ouarti (2008) excludes the possibility that the luminance gradient, always correlated with the perspective tilt axis, guided saccade directions in that and the current study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our results for saccades extend those recently published by Wexler and Ouarti (2008), who showed that spontaneous saccade directions follow the tilt axis of an inclined plane, for a variety of depth cues that were presented singly (other recent work that reports compatible results is Jansen, Onat, & König, 2009). The fact that spontaneous saccade directions are aligned with the surface depth gradient of a purely disparity-defined plane as shown by Wexler and Ouarti (2008) excludes the possibility that the luminance gradient, always correlated with the perspective tilt axis, guided saccade directions in that and the current study.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that spontaneous saccade directions are aligned with the surface depth gradient of a purely disparity-defined plane as shown by Wexler and Ouarti (2008) excludes the possibility that the luminance gradient, always correlated with the perspective tilt axis, guided saccade directions in that and the current study. Earlier, Vishwanath and Kowler (2004) reported that saccade landing positions were related to the 3D geometric cues of the saccade targets revealing that depth cues are important in driving saccades, whereas luminance has been shown to have at the most a moderate effect on saccade landing positions (Melcher & Kowler, 1999;Spering, Montagnini, & Gegenfurtner, 2008).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations